Right-sided omental torsion with inguinal hernia - Deng, Liming; Xiong, Guozuo; Yan, Yaping; Dai, Xianpeng; Xin, Shen; Bi, Guoshan; Chen, Jie; Hu, Bingbing; Wu, Wengao; Li, Linpeng (International Surgery Journal, 2016)
A 38 year old man was admitted to our hospital with abdominal pain. He had an untreated right inguinal hernia and the hernia presented as a swelling ball of 4.0×3.0 cm in size. CT showed a large mass of fat density below the Sigmoid colon and incarcerated fat within the right inguinal hernia. Emergent laparotomy revealed four-circle twisted and infarcted greater omentum and a little bloody ascites within the right inguinal hernia. Pathological examination showed hemorrhagic infarction of the greater omentum. Although omental torsion is a rare cause of acute abdominal pain, it should be taken into consideration in the differential diagnoses of acute abdomen, especially in patients with untreated inguinal hernia.